Highly stable tandem solar cell monolithically integrating dye-sensitized and CIGS solar cells - Chae, Sang Youn (Sci Rep, 2016)
A highly stable monolithic tandem solar cell was developed by combining the heterogeneous photovoltaic technologies of dye-sensitized solar cell (DSSC) and solution-processed CuIn(x)Ga(1-x)Se(y)S(1-y) (CIGS) thin film solar cells. The durability of the tandem cell was dramatically enhanced by replacing the redox couple from [Image: see text] to [Co(bpy)(3)](2+) /[Co(bpy)(3)](3+)), accompanied by a well-matched counter electrode (PEDOT:PSS) and sensitizer (Y123). A 1000 h durability test of the DSSC/CIGS tandem solar cell in ambient conditions resulted in only a 5% decrease in solar cell efficiency. Based on electrochemical impedance spectroscopy and photoelectrochemical cell measurement, the enhanced stability of the tandem cell is attributed to minimal corrosion by the cobalt-based polypyridine complex redox couple.